2011
DOI: 10.1590/s0102-09352011000300024
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de ovos comerciais submetidos a diferentes condições de armazenamento

Abstract: Qualidade de ovos comerciais submetidos a diferentes condições de armazenamento

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
31

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 14 publications
6
15
0
31
Order By: Relevance
“…In a study evaluating eggs stored for up to 35 days, Barbosa et al (2008) observed an average 9.20% reduction in the weight of eggs stored in a high temperature and moisture environment. Similar findings were reported by Figueiredo et al (2011), who verified greater egg weight loss, from 0.65g to 1.03g, in eggs stored at 21ºC for 5 and 10 days, respectively. Haugh units were affected by the interaction (p<0.01) between trace mineral source and storage period.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In a study evaluating eggs stored for up to 35 days, Barbosa et al (2008) observed an average 9.20% reduction in the weight of eggs stored in a high temperature and moisture environment. Similar findings were reported by Figueiredo et al (2011), who verified greater egg weight loss, from 0.65g to 1.03g, in eggs stored at 21ºC for 5 and 10 days, respectively. Haugh units were affected by the interaction (p<0.01) between trace mineral source and storage period.…”
Section: Resultssupporting
confidence: 90%
“…Oliveira et al (2009) observed greater losses in egg internal when eggs were stored at 25ºC compared with 6ºC for 30 and 50 days, respectively. Similar results were obtained by Figueiredo et al (2011) when storing eggs for up to 15 days at different temperatures (2.6ºC±0.9ºC and 25.6ºC±1.7ºC). There was no effect (p>0.05) of the evaluated treatments on raw yolk color.…”
Section: Trace Mineral Sources and Rosemary Oil In The Diet Of Brown supporting
confidence: 84%
“…This is probably due to the age of the bird and the temperature. However, Figueiredo et al (2011), found that eggs kept at room temperature presented lower weight than chilled eggs due to the laying age, time and temperature. Laganáet…”
Section: Performance Of Commercial Laying Hen Submitted To Different mentioning
confidence: 98%
“…A quantidade de cálcio depositada nos ovos permanece mais ou menos constante durante todo o ciclo de postura; todavia, do início ao final do ciclo de postura o ovo chega a aumentar até 40% do seu tamanho razão por que haverá menos cálcio por área de superfície de casca o que resultará na redução da resistência da casca; assim, aves jovens têm uma taxa de retenção de aproximadamente 60% enquanto as aves mais velhas retêm apenas 40% do cálcio absorvido (Oliveira et al, 2009;Costa et al, 2011;Figueiredo et al, 2011).…”
Section: Figura 1 Distribuição Fixa Dos Acelerômetros (Caixas Pretasunclassified
“…Sabe-se que a casca do ovo apresenta apenas 0,01 de água (Nascimento & Salle, 2003;Figueiredo et al, 2011). Portanto, a quantidade de água presente na casca do ovo era muito pequena para resultar em trincas.…”
Section: Figura 1 Distribuição Fixa Dos Acelerômetros (Caixas Pretasunclassified